Ovary development in honeybee (Apis Mellifera L.) workers under co2 narcosis, caged outside of the colony - Berger, Bruno [UNESP]; Poiani, Silvana B. [UNESP]; Roat, Thaisa C. [UNESP]; Cruz-Landim, Carminda da [UNESP] (Research Inst Pomology Floriculture, Div Apiculture, 2015)
Exposure of A. mellifera workers to CO2 has been reported to decrease life span, induce behavioral changes, and inhibit the development of some glands and the ovaries. However, the use of CO2 is currently practiced among beekeepers and how the development of workers'ovaries are affected is unknown. The present work aimed to evaluate the effect of CO2 on the ovaries of A. mellifera workers, using a morphological approach. Newly emerged, and 3, 5, and 10-day-old workers were exposed to saturated CO2 for 30 seconds, more than once. The ovaries were examined under light (LM) and transmission electron microscopy (TEM). The ovaries of narcotized, 5-day-old workers exhibited long ovarioles with well-developed germarium, although oogenesis showed little development. While in the control group, the ovaries already exhibited cysts with cystocytes forming rosettes. At 10-days-old, the ovaries feature was variable; some of the ovaries showed ovarioles with many rosette cysts while others showed a high intensity of disorganization due to the beginning of cell death. The ovarioles of the ovaries of 15-day-old treated workers were morphologically varied as oogenesis showed little or no advance. In others cases, a complete disorganization with swollen cells and cell death features were observed. Germ cells of the ovaries of CO2-treated workers exhibited well-structured organelles, such as the Golgi complex, and larger amounts of mitochondria in the cytoplasm than the control group, but there was disorganization of the endoplasmic reticulum membranes. Our findings revealed that the exposure of workers to CO2 promotes impairment of oogenesis and ovarian degradation.
Keywords: anesthesia; cell death; eusocial insects; light microscopy; oogenesis; transmission electron microscopy